La lactancia materna y su relación con el desarrollo de las maloclusiones - Guacho Lamar, Ximena Alexandra (2022)
Breastfeeding is the ideal feeding for the development of the infant, so we consider it fundamental for the growth and development of the jaws since, employing the functional activity and the stimulation of the orofacial structures, which takes place inside the oral cavity, we can avoid the appearance of alterations such as dental malocclusions. Breastfeeding; not only contributes to the correct development of the orofacial structures; but also, the correct positioning of the incisors and the sagittal and vertical relationship of the mandible and maxilla. The present study is of an analytical and documentary type, so we carried out its elaboration through the search of 45 scientific articles obtained in databases such as Scielo, Google Scholar, PubMed, Multimedic, Medigraphic, ElSevier, Books and Repositories of national and international Universities, on breastfeeding and its relationship with the development of malocclusions. After analyzing the information, a significant relationship was found between breastfeeding and the development of malocclusions. Adequate breastfeeding is an important stimulus in the growth of the jaws, guaranteeing 100% of the development of a normal occlusion; on the contrary, when breastfeeding is by means of a bottle, the child tends to develop a transverse micrognathism. Likewise, the time of breastfeeding is a significant factor, since breastfeeding for a period longer than six months shows a better prevalence in terms of Angle class I (43.60%), canine class I (61.95%) and a decrease in other types of malocclusions such as anterior crossbite (7.73%) and anterior open bite (1.60%). In relation to artificial breastfeeding, there was a higher prevalence of Angle class II (61%), canine class II (37.50%) and an increase in other types of malocclusions such as anterior crossbite (12.20%) and anterior open bite (1.90%), with the exception of posterior crossbite which was recorded at 1.35%. Keywords: Breastfeeding, Malocclusion, Maxillofacial Development, Prenatal, Jaw Abnormalities.